A Tribute to Samuel J. Zacks from the Sam and Ayala Zacks Collection. - Zacks, Ayala; Welsh, Robert; National Gallery of Canada, Ottawa (Toronto : Art Gallery of Ontario, 1971)
Chaim, Soutine ; Rouault, Georges ; Chagall, Marc ; De Chirico, Giorgio ; Derain, André ; Braque, Georges ; Picasso, Pablo ; Metzinger, Jean ; Gris, Juan ; Léger, Fernand ; Delaunay, Robert ; Severini, Gino ; Balla, Giacomo ; Janco, Marcel ; Villon, Jacques ; Picasso, Pablo ; etc.
A Tribute to Samuel J. Zacks from the Sam and Ayala Zacks Collection, Art Gallery of Ontario, Toronto, May 21 - June 27, 1991 ; National Gallery of Canada, Ottawa, August 2 - August 31, 1971
kunstcatalogus